A Thermal-Hydraulic-Mechanical Coupling Study of Heat Extraction from the Geothermal Reservoir with a Discrete Fracture Network. (23rd November 2020) - Ye, Zhiwei; Wang, J. G.
Abstract : The complex thermal-hydraulic-mechanical (THM) coupling is the key issue to the energy extraction from a geothermal reservoir, where fractures are the main channels for fluid circulation and heat transfer. However, the effects of matrix deformation-induced aperture variation and fracture roughness on heat recovery efficiency are unclear. In this paper, a fully coupling THM model based on a discrete fracture network is proposed to explore these coupling effects. First, the fracture roughness and the fracture aperture variation with effective stress are introduced. Second, the water flow and heat transfer in the matrix and fractures as well as the deformation of the geothermal reservoir are individually formulated for a fractured geothermal reservoir. Third, the model is validated with analytical solution for its thermal-hydraulic (TH) coupling effect and literature data for its hydraulic-mechanical (HM) coupling effect. Finally, the features of heat transfer and fluid flow in the fractured geothermal reservoir are comparatively analyzed through four scenarios. The simulation results indicate that the discrete fracture network severely impacts the pressure distribution and temperature advance. The aperture variation induced by solid deformation can enhance heat transfer efficiency, and the fracture roughness can reduce the heat transfer efficiency.